Pengaruh Pendapatan Asli Daerah, Belanja Daerah dan Kompleksitas Pemerintahan Terhadap Transparansi Informasi Keuangan Daerah Via Website - Sophi Dezalinda; Mayar Afriyenti (Jurnal Buana Akuntansi, 2023)
This study aims to provide empirical evidence of the effect of regional original income, regional spending and government complexity on the transparency of regional financial information via websites in Indonesia. This study examines the transparency of financial information on the websites of 84 provincial governments in Indonesia based on the availability and accessibility of this information. This study was tested using 2 methods, namely the regression method for availability and the multiple regression method for the accessibility of financial information on the provincial government website. According to the findings of this study, regional own-source revenues have a beneficial and sizeable impact on financial transparency. Meanwhile, regional spending and government complexity have no effect on the transparency of the regional financial data website. The findings of this study reinforce the agency theory, namely that high local revenue indicates the government's success in carrying out its duties and responsibilities to the community. This research can help the government by providing quantitative empirical evidence about the effect of local original income on the transparency of regional financial information through websites, thereby enabling the government to be more open with other financial information.